Impact of the Arg 16 allele of the B2AR gene on the effect of withdrawal of LABA in patients with moderate to severe asthma. (13th September 2016) - Slankard, Marjorie; Michelis, Mary Ann; Mansukhani, Mahesh; McGoey, Barbara; Paige, Amy; Andrews, Howard; Lederer, David; Canfield, Stephen; DiMango, Emily
Abstract: Introduction : Long-acting beta agonists (LABAs) are effective for controlling asthma, however questions about their safety have led to concerns over use. Genetic polymorphisms at the 16 amino acid position of the beta-2 adrenergic receptor gene (B2AR) may be associated with increased risk. Methods : A randomized, double blind study was conducted in patients with moderate to severe asthma being treated with combined inhaled corticosteroids/LABA (ICS/LABA), comparing the effect of LABA continuation versus withdrawal on asthma outcomes among patients stratified by B2AR genotype (Arg/Arg vs. Gly/Gly at the 16th amino acid position). Results : 67 participants (31 Arg/Arg, 36 Gly/Gly) were randomized to receive fluticasone alone (F) or continue combined fluticasone/salmeterol (F/S) after a run-in period on F/S. Among Gly/Gly subjects, those in the F/S treatment group showed improvement in AM PEFR (+ 8.4 L/s) whereas those receiving F alone experienced a reduction in AM PEFR over the study period (−14.4 L/s), ( p = 0.06). There was no significant difference in morning peak expiratory flow rate (AM PEFR) in Arg/Arg participants randomized to receive F/S (−15.7L) vs F alone (−5.6 L/s) ( p = 0.61). There was no significant difference in exacerbations in the Arg/Arg subjects treated with F/S compared with those treated with F ( p = 0.65). Conclusions : Withdrawal of LABA therapy in asthmatics with the Arg/Arg genotype at the 16th amino acid position of B2AR did not lead to significant improvement in AM PEFR. LABA withdrawal in the Gly/Gly genotype however led to a borderline significant decline in AM PEFR.